Thread and communication a visual manifestation of re-connecting with a dear departed - Astejada, Samuel Bien Sandro T.; Concepcion, Reynaldo L. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Reconnecting with a dear departed is what every person left behind wishes for. Such is the wish of this proponent. The death of his parents is so heartbreaking that the loss made him withdrew for a while from the world he used to live in with his parents and retreated to a place of isolation. While in that place, he developed a way to cope with his loss: he started to write his thoughts on pages of notebooks and journals, words that he would have spoken to his parents if they were still alive. In his own way, he kept a "connection" with his departed parents through his writings on pages of paper.

This thesis attempts to create a visual representation of the virtual connection he maintained for years with his departed parents. He attempts to visually connect the written words on the paper using the linear quality of thread as a medium and metaphor for the "conversations" he wished he had with his parents. Each thread represents a word and it will unravel, travel, a distance, and converge with other threads to a spot where they will form the image of his parents.

Reconnecting with a dear departed requires a leap of faith, a strong belief in the spiritual. As an artist, he wants to create another way to send the words he has written to his parents -- figuratively speaking, another line to heaven.
Thesis (Bachelor of Fine Arts in Painting)--University of the Philippines Diliman
Bibliography: leaves 17-18
Keywords: Parent and child; Parents -- Death; Reconnection; Embroidery; Thread